Congregations and Social Services: An Update from the Third Wave of the National Congregations Study - Chaves, Mark (Religions, 2016)
Congregations and other religious organizations are an important part of the social welfare system in the United States. This article uses data from the 2012 National Congregations Study to describe key features of congregational involvement in social service programs and projects. Most congregations (83%), containing 92% of religious service attendees, engage in some social or human service activities intended to help people outside of their congregation. These programs are primarily oriented to food, health, clothing, and housing provision, with less involvement in some of the more intense and long-term interventions such as drug abuse recovery, prison programs, or immigrant services. The median congregation involved in social services spent $1500 per year directly on these programs, and 17% had a staff member who worked on them at least a quarter of the time. Fewer than 2% of congregations received any government financial support of their social service programs and projects within the past year; only 5% had applied for such funding. The typical, and probably most important, way in which congregations pursue social service activity is by providing small groups of volunteers to engage in well-defined and bounded tasks on a periodic basis, most often in collaboration with other congregations and community organizations.